2015
DOI: 10.1111/his.12722
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic stromal tumour of the ovary: frequent mutations of β‐catenin (CTNNB1) in six cases

Abstract: MCST shows a unique morphology with characteristic immunophenotype. β-catenin expression in the nucleus and β-catenin mutations were identified in the majority of cases, which suggests that the Wnt/β-catenin pathway may play a crucial role in the tumorigenesis of MCST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…Nuclear staining was present in all but one of the 30 MCSTs, which showed cytoplasmic-only staining but did contain a CTNNB1 mutation. 61 Overall, 76% (22/29) of MCSTs with nuclear pattern bcatenin staining contained a CTNNB1 mutation. Comparison of the clinicopathological features of CTNNB1mutated MCST with those of CTNNB1 without mutation has not been described in these studies.…”
Section: T N N B 1 a N D M C S Tmentioning
confidence: 94%
See 3 more Smart Citations
“…Nuclear staining was present in all but one of the 30 MCSTs, which showed cytoplasmic-only staining but did contain a CTNNB1 mutation. 61 Overall, 76% (22/29) of MCSTs with nuclear pattern bcatenin staining contained a CTNNB1 mutation. Comparison of the clinicopathological features of CTNNB1mutated MCST with those of CTNNB1 without mutation has not been described in these studies.…”
Section: T N N B 1 a N D M C S Tmentioning
confidence: 94%
“…A somatic mutation of CTNNB1 exon 3 has been reported in 73% (22/30) of MCSTs . The mutation was missense in all but one case, which was a deletion mutation .…”
Section: Mcst and Ctnnb1 And Apcmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, in a recent study of 10 microcystic stromal tumours, we identified CTNNB1 and APC mutations in eight and two cases, respectively . Mutations in CTNNB1 and APC genes are mutually exclusive in microcystic stromal tumour and they result directly in nuclear immunoreactivity with beta‐catenin and cyclin D1 through activation of the Wnt signalling pathway . Herein, we report four ovarian neoplasms with a different morphology but an identical immunophenotype and molecular events to microcystic stromal tumour.…”
Section: Introductionmentioning
confidence: 94%